Can early vigour occur in combination with drought tolerance and efficient water use in rice genotypes? - Rebolledo, María Camila; Luquet, D; Courtois, Brigitte; Henry, A; Soulie, JC; Rouan, L; Dingkuhn, Michael (Commonwealth Scientific and Industrial Research Organisation, 2013)
Selection for early vigour can improve rice (Oryza sativa L.) seedlings’ access to resources, weed competitiveness and yield. Little is known about the relationships between early vigour and drought tolerance. This study explored a panel of 176 rice genotypes in a controlled environment regarding a diversity of traits and trait combinations related to early vigour and water use under drought. The design excluded genotypic differences for root depth. We hypothesised that early vigour (as determined by biomass accumulation under well-watered conditions) was not independent from drought tolerance (determined by biomass accumulation maintenance under drought). Leaf size, developmental rate (DR) and tiller number contributed positively to shoot DW and leaf area, and thus vigour. Early vigour was negatively correlated with growth maintenance and water use efficiency under drought, suggesting tradeoffs. Three clusters of genotypes were identified based on the constitutive traits DR, specific leaf area, tiller number and leaf size. The less drought-tolerant cluster, mainly with lowland O. sativa indica rices, showed a sensitive transpiration response to the fraction of transpirable soil water; however, under well-watered conditions these genotypes were vigorous, with small leaves, high DR and high tillering. This experiment showed that the tradeoff between early vigour and drought tolerance was physiological and not a matter of access to water. The results are discussed with a view to identify drought adaptation strategies for crop improvement. Further improvement of multitrait phenotyping approaches is proposed.